Crabgrass Control in Spring Seeding Using Early and Late Combinations of Prodiamine and Dithiopyr - J. Hoyle; J. Reeves (Kansas Agricultural Experiment Station Research Reports, 2015)
With less crabgrass pressure, the Kansas site showed an inhibitory effect of pre-emergent herbicides on spring tall fescue (Lolium arundinaceum) seeding and establishment. However, at the Nebraska site, greater crabgrass pressure showed a benefit of pre-emergent herbicide use in new spring seeding of tall fescue.
Keywords: turfgrass; Digitaria spp.; crabgrass control; prodiamine; dithiopyr; pre-emergent herbicide; spring tall fescue; Lolium arundinacea